Changing epidemiology of gastroesophageal reflux disease in the Asian-Pacific region: an overview. - Goh, K.L. (Blackwell Publishing, 2004)
Gastroesophageal reflux disease (GERD) is a common disease in the West, which now appears to be also increasing in prevalence in the Asian Pacific region. The reasons for this changing epidemiology are two-fold: an increased awareness among doctors and patients, and/or a true increase in the prevalence of the disease. Prevalence rates of reflux esophagitis (RE) of up to 16% and prevalence of GERD symptoms of up to 9% have been reported in the Asian population. However, the frequency of strictures and Barrett's esophagus remain very low. Non-erosive reflux disease (NERD) appears to be the most common form of GERD among Asian patients accounting for 50-70% of cases with GERD. Among Asian patients differences can also be discerned among different ethnic groups. For example, in Malaysia where a multiracial society exists, RE is significantly more common among Indians compared to Chinese and Malays whereas NERD is more frequently seen in the Indian and Malays compared to the Chinese. The reasons for these differences are not known but may indicate both genetic factors and environmental factors peculiar to the particular racial group. GERD has also been increasing in the region demonstrating a time-lag phenomenon compared to the West. Differing predisposition to GERD among different ethnic groups would mean that such an increase would be more prominent among certain racial groups.